2023
DOI: 10.18231/j.jdpo.2023.018
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on cervical cancer screening- In a newly opened tertiary care Centre in Eastern India

Abstract: : One of the most prevalent cancers, cervical cancer is also the leading cause of mortality for women in underdeveloped nations. A fundamental test for finding infections and precancerous diseases is the Papanicolaou smear. This study aims to comprehend the function of cervical screening in detecting premalignant, malignant, and non-neoplastic lesions as well as the prevalence of different lesions in women who received a traditional pap smear technique. We screened women in the age group of 15-70 years who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…13 In the study conducted by Pandey et al, 79 cases (3.7%) were atrophic smears, which was in line with this study, where 23 cases were (3.9%) atrophic smears. 12 In the study conducted by Sinchana et al, 18 cases (9%) were reported as ECA, which were in line with this study, where 53 cases (9%) were also reported as ECA. 11 In a study conducted by Sharma et al, in 2021, the total number of ASCUS cases was 15 (3.3%), which was in line with this study where 21 cases (3.74%) were reported as such.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…13 In the study conducted by Pandey et al, 79 cases (3.7%) were atrophic smears, which was in line with this study, where 23 cases were (3.9%) atrophic smears. 12 In the study conducted by Sinchana et al, 18 cases (9%) were reported as ECA, which were in line with this study, where 53 cases (9%) were also reported as ECA. 11 In a study conducted by Sharma et al, in 2021, the total number of ASCUS cases was 15 (3.3%), which was in line with this study where 21 cases (3.74%) were reported as such.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted by Pandey et al, in 2023Pandey et al, in , 1987 cases (93.2%) were reported as Negative for Intraepithelial Lesion or Malignancy, which was a line in this study, where 525 cases (91%) were reported as Negative for Intraepithelial Lesion or Malignancy. 12 In the study conducted by Sinchana et al, 139 cases (69.5%) were smears associated with inflammation, whereas in this study, 353 cases (57.4%) were inflammatory smears. 11 Cases with persistent inflammation must be further evaluated and treated appropriately as they may slowly transform into pre-malignant lesions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation